2016
DOI: 10.1186/s12879-016-2035-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, antimicrobial susceptibility patterns and associated risk factors of Shigella and Salmonella among food handlers in Arba Minch University, South Ethiopia

Abstract: BackgroundThe availability of safe food improves health of the people that contributes to productivity and provides an effective platform for development and poverty alleviation. On the other hand, unsafe food handling and processing can serve as a vehicle for the transmission of a variety of disease causing agents. The risk of food getting contaminated depends largely on the health status of the food handlers, their personal hygiene, knowledge and practice of food hygiene. Food borne diseases are therefore a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

61
58
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(125 citation statements)
references
References 13 publications
61
58
5
1
Order By: Relevance
“…among food handlers who had more than 5 years’ work experience (61.9%) compared to less than or equal to 5 years (38.1%). This is in line with a study done in Arba Minch University, Ethiopia (32.4%) [20]. However, the results are lower compared to a study done in Mekelle University, Ethiopia in which 60% of food handlers who served for less than 5 years were infected [12].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…among food handlers who had more than 5 years’ work experience (61.9%) compared to less than or equal to 5 years (38.1%). This is in line with a study done in Arba Minch University, Ethiopia (32.4%) [20]. However, the results are lower compared to a study done in Mekelle University, Ethiopia in which 60% of food handlers who served for less than 5 years were infected [12].…”
Section: Discussionsupporting
confidence: 87%
“…The finding is comparable to a study conducted in Addis Ababa University, Ethiopia (3.4%) [19]; but relatively higher than reports from other parts of Ethiopia, such as Dilla University (0.93%) [8] and Mekelle University (1%) [12]. However, it is lower compared with a study done in Arba Minch University, Southern Ethiopia (6.9%) [20] and Bahir Dar, Ethiopia (80%) [4]. On the other hand, a higher rate of Shigella spp.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…This finding is in line with the result obtained from the previous study done in Debre Markos Ethiopia [13]. However, this was in contrary with the findings from Addis Ababa and Arba Minch University, South Ethiopia [31, 32] where no statistical significant association between bacterial isolation and service was seen. This result indicated that food handlers with more work experience have less risk of bacterial finger nail isolation.…”
Section: Discussionsupporting
confidence: 83%
“…The sample size was determined based on the prevalence of Salmonella among university food handlers done by Mama and Alemu (2016) at Arba Minch University, South Ethiopia (6.9%) [14]. Then with a margin of error (5%), (d=0.03) and 95% level of con dence (z=1.96), the sample size was calculated as follows: See formula 2 in the supplementary les.…”
Section: Sample Size Determinationmentioning
confidence: 99%